Online Courses in the Higher Education System of Iran: A Stakeholder-Based Investigation of Pre-Service Teachers’ Acceptance, Learning Achievement, and Satisfaction - Dashtestani, Reza (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
This study focused on the acceptance level of higher education stakeholders of teaching English as a foreign language (TEFL) of online courses in Iran and pre-service teachers’ learning achievement in online courses. Three cohorts of participants who were teaching or learning in online courses included pre-service teachers of TEFL (n=104), TEFL university instructors (n=23), and heads of TEFL departments (n=10). A questionnaire was designed. The Kruskal Wallis test was used to detect differences among the perspectives of the participants. Semi-structured interviews were also utilized. Results indicated that there were significant differences among the perspectives of the three groups of participants about online courses. The pre-service teachers appeared to be relatively positive about online learning, while the university instructors and heads of departments showed a lower level of satisfaction. The participants pointed out several challenges, including the lack of rigor of online courses, the incredibility of the certificates, the lack of technological infrastructures, technical problems, the impractical content of the lessons, the lack of human interaction, the low competence levels of online learning students, and employers’ lack of interest in employing graduates of online courses. The participants also mentioned that pedagogical and technological training was required for both university instructors and pre-service teachers of TEFL. The comparison of pre-service teachers’ mid-term and final scores in the online courses showed a significant difference and improvement of students’ learning achievement in online courses with medium to large effect sizes. In the interviews, the participants also confirmed that online courses could improve student learning.